Chapter 7. Diversity: measurement and valuation - Santos, Jorge (Septentrio Educational, 2015)
This chapter of CONΣERV IT deals with the following questions in aquatic conservation: - What do ecologists call diversity? - How can we measure changes in diversity in locally impacted areas? - How can we valuate those changes by simple means? Conservation and valuation of diversity Belize